Interdisciplinary research in dialogue with isleñx villagers of the lower Delta of the Paraná Organdxs in defense of its territory and its ways of life - Glustein, Jazmín; Borón, Carlos Ignacio; Saveika, Camila; Carrillo Pinto, Cecilia; Falcón, María de los Ángeles; Sirolli, Horacio; Larrandart, Sofía; Ostertag, Camila; Jatar, Lara; Mordiero, Julieta; Bazylenko, Andrey; Do Campo, Margarita (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
In 2008, the emblematic socio -environmental conflict originated by the progress of a closed urbanization over 365 ha of island territory, in the Anguilas stream, Delta del Río Paraná, Tigre Party. The company Col Col Park S.A. Performs a first stage of dredging works, widening of the stream, clearing and fillings without having the required administrative permits, or environmental impact study presented. In addition, he directs actions of intimidation, harassment and destruction of the housing of Junqueras and fishermen residents in the Anguilas stream, ignoring his right over these lands (Cooperativa Isla Esperanza, 2013; Astelarra, 2015, 2017). This interdisciplinary work group is formed in order to evaluate the current environmental situation after 10 years of the Judicial Closing of the Colony Park project. Changes in free water and surface coverage were studied in the Linking Canal area and the San Antonio, Luján and Río de la Plata rivers. In turn, the spontaneous vegetation developed in the place since then was characterized. On the other hand, chemical and microbiological analyzes of water from the Anguilas stream and other nearby courses were carried out with the aim of determining its aptitude for consumption, purification and recreational use. Likewise, environmental education activities were designed and implemented together with island schools, where these themes were addressed. Participatory research-action strategies were applied together with members of the Isla Esperanza cooperative and other residents of the area to approach the various aspects of the project in a participatory manner, promoting a dialogue between academic and local knowledge. From the results obtained, the working group considers a priority to sustain the claim of public policies agreed with the island population that recognizes the current situation and stop the environmental degradation of the territory.